Meteorological data from Grimsö, AWS, 2018-01-01–2018-12-31 - Grimsö Wildlife Research Station (Swedish University of Agricultural Sciences, 2025)
Automatic weather station data from locations within the distributed Swedish research infrastructure SITES. Check preview or file for the specific parameters included at this location. Data has been quality controlled and cleaned from outliers and other events producing unrealistic data. Gaps have not been filled.
Grimsö Wildlife Research Station (2025). Meteorological data from Grimsö, AWS, 2018-01-01–2018-12-31 [Data set]. Swedish Infrastructure for Ecosystem Science (SITES). https://hdl.handle.net/11676.1/-2JQ9TLZxKdLFmMAotbY4V3X
Keywords: Grimsö Wildlife Research Station; Atmospheric radiation; Humidity; Precipitation; Surface Winds; Time instant; Time instant; Air temperature; Air temperature; Relative humidity; Relative humidity; Wind speed; Wind speed; Wind direction; Wind direction; Incoming shortwave radiation; Incoming shortwave radiation; Soil Science; Markvetenskap; Agriculture, Forestry and Fisheries; Jordbruk, skogsbruk och fiske; Agricultural Science; Jordbruksvetenskap; Ecology; Ekologi; Multidisciplinary Geosciences; Multidisciplinär geovetenskap; Environmental Sciences; Miljövetenskap; Climate Science; Klimatvetenskap